Od diagnozy do towarzyszenia w żałobie – wsparcie rodzin z dzieckiem z wadą letalną - JARZĘBIŃSKA, ANETA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Aneta Jarzębińska, Od diagnozy do towarzyszenia w żałobie – wsparcie rodzin z dzieckiem z wadą letalną [From the diagnosis to the accompanying in mourning– support from the families of children with lethal defect]. Interdyscyplinarne Konteksty Pedagogiki Specjalnej, nr 22, Poznań 2018. Pp. 375-391. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.22.21 This article characterizes the interactions and institutions in which parents can receive support after their child has been diagnosed with a lethal defect. First and foremost parents need information and emotional support when making decision regarding their child. The primary source of the aforementioned elements is the hospital personnel and the perinatal hospice- that is if parents decide to contact it. If the child is born alive and discharged from the hospital then the parents require support during its treatment (which more often than not is identical with palliative care) and rehabilitation, even social rehabilitation. Children’s hospices can offer many services in this particular matter. On each stage of the child’s disease the contact with other parents of children with lethal defect is crucial. They can negate the feeling of isolation, give practical advice regarding the situation and most of all give hope that even though the prognosis is fatal some of the children lived.